Model Bimbingan Guru Pendidikan Agama Kristen dalam Pendidikan Karakter Kristiani Siswa di SMA Negeri 1 Tamako Kabupaten Kepulauan Sangihe - Retnosari Lakada; Jeane M. Tulung; Heldy J J. Rogahang (Peneliti.net, 2021)
The purpose of this study is to describe the model of Christian religious education teacher guidance in student character education. This research was motivated by problems that occur in schools regarding the character of students who are very concerned such as saying dirty words, fighting, truancy, carrying sharp weapons, smoking, drinking. - liquor and so on. This research is a qualitative research with a descriptive method, which was conducted in Senior High School 1 Tamako, Sangihe Islands Regency. Researchers collected data through observation, interviews and documentation study to those who ware considered to be able to provide accurate information. From the results of data analysis, it was concluded that individual Christian religious education teacher guidance was only carried out for students with problems, guidance to all students was carried out through sermons during school worship. From these findings, it is hoped that this research can provide new understanding and knowledge for Christian Religious Education teachers regarding guidance for character education of students so that problems regarding the character of students in schools can be resolved.